2018
DOI: 10.2147/jpr.s154661
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone and clavulanic acid induce antiallodynia and anti-inflammatory effects in rats using the carrageenan model

Abstract: IntroductionCeftriaxone (CFX) and clavulanic acid (CA) are 2 β-lactam molecules widely used as antibiotics. However, several reports of their antiallodynic properties have been published in recent years. Although this effect has been considered mostly due to a GLT1 overexpression, these molecules have also been proven to induce direct immunomodulation. In this work, we determine the acute analgesic effect of CFX and CA in an inflammatory pain model and assess if their administration may induce anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Surprisingly, we found that CFX did not reach more than 30% of antinociceptive effect. These results partially agree with some reported data in inflammatory pain (Ochoa-Aguilar et al, 2018;Stepanovic-Petrovic et al, 2014). The small effect observed in our conditions could be related to the participation of different mechanism in the different models.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Surprisingly, we found that CFX did not reach more than 30% of antinociceptive effect. These results partially agree with some reported data in inflammatory pain (Ochoa-Aguilar et al, 2018;Stepanovic-Petrovic et al, 2014). The small effect observed in our conditions could be related to the participation of different mechanism in the different models.…”
Section: Discussionsupporting
confidence: 94%
“…To our knowledge, this is the first report about the antinociceptive effect of CFX in a formalin test (1%) model, which implies an inflammatory component. Our data agree with previous studies assessing the antinociceptive effect of CFX in models of inflammatory pain, such as carrageenan, acetic acid, and surgical incision (Macaluso et al, 2013;Ochoa-Aguilar et al, 2018;Stepanovic-Petrovic et al, 2014). Moreover, it has been reported that CFX is partially effective in models of neuropathic pain in rodents (Amin et al, 2012;Eljaja et al, 2011;Gunduz et al, 2011;Hajhashemi et al, 2013;Hu et al, 2010;Ochoa-Aguilar et al, 2017;Pottabathini et al, 2016;Ramos et al, 2010;Shi et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increases in GLT-1 levels and a reduction of chronic ethanol intake following the administration of β-lactam antibiotics have also been reported by Sari and associates in rats selected as alcohol drinkers (Rao et al, 2015 ; Sari et al, 2016 ). Recent and previous studies also indicate that the β-lactam ceftriaxone displays anti-inflammatory effects (Amin et al, 2012 ; Ochoa-Aguilar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 89%